Reverse engineering of planar objects using gas - Muhammad Sarfraz,; Misbah Irshad,; Malik Zawwar Hussain, (Universiti Kebangsaan Malaysia, 2013)
An automatic approach, for reverse engineering of digitized hand printed and electronic planar objects, is presented which is useful for vectorizing the generic shapes. The rational cubic functions were used to find the optimal solution of the curve fitting problem with the help of a soft computing technique genetic algorithm which finds appropriate values of shape parameters in the description of rational cubic functions.